2017
DOI: 10.1021/acs.langmuir.7b02414
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrodeposition of Tantalum(V) Oxide Electrodes

Abstract: Thin films of TaOH were cathodically electrodeposited from an aqueous solution containing Ta-IPA precursor and KNO as a sacrificial agent. It was shown that the deposition resulted from a precipitation reaction triggered by the local change of pH at the surface of working electrode. Combined structural and compositional analysis revealed that during the electrodeposition the oxidation state of tantalum remained constant, Ta(V). The as-deposited films are mesoporous amorphous tantalum oxide hydrate films, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Primary nanoparticles of oxide catalysts can be prepared, but these fine particles easily aggregate to form larger secondary particles during high-temperature preparation [16]. For this reason, electrodeposition methods have been commonly used to control the size and distribution of metal particles of Ta-based materials on conductive substrates [17,19,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Primary nanoparticles of oxide catalysts can be prepared, but these fine particles easily aggregate to form larger secondary particles during high-temperature preparation [16]. For this reason, electrodeposition methods have been commonly used to control the size and distribution of metal particles of Ta-based materials on conductive substrates [17,19,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic technology offers an opportunity to overcome the problem. Titanium dioxide as a classical photocatalyst is widely used, but it has some shortcomings (low utilization of solar energy), which seriously limit its practical application. Therefore, designing a new and efficient photocatalyst to utilize visible light is the focus in the current study of photocatalysis. Bismuth vanadate (BiVO 4 , n-type semiconductor) attracts increasingly bigger attention due to its excellent chemical stability, nontoxicity, and so on. , However, further improving photocatalytic performance is necessary due to its low ability to separate electron–hole pairs. …”
Section: Introductionmentioning
confidence: 99%
“…Zhitomirsky , showed that one strategy to circumvent the high reactivity of NbCl 5 with water is to first form a stable niobium peroxo complex precursor and then subsequently generate base in an aqueous electrolyte to precipitate amorphous Nb 2 O 5 . Similarly, Hajibabaei and Hamann recently reported on the precipitation of Ta 2 O 5 from a tantalum isopropoxide precursor, formed by mixing TaCl 5 and isopropanol in an aqueous electrolyte, upon electrogeneration of base. However, both methods require an intermediate synthetic step and produce nonuniform coatings with large grains and cracks, rendering them unsuitable for optical applications.…”
Section: Introductionmentioning
confidence: 99%